Model of diagnosis and prognosis of mental disorders in patients with rheumatoid arthritis - Yuryeva, Людмила; Nikolenko, Алла; Nosov, Сергій (Psychosomatic Medicine and General Practice, 2022)
Topicality. Rheumatoid arthritis (RA) is a stress-dependent disease, so exposure to a long-term psychotraumatic situation, such as the war in Ukraine, can lead to an increase in the number of RA onsets and exacerbations. The prevalence and incidence of psychiatric disorders in rheumatoid arthritis, especially depression and anxiety, are known to be high and exceed those in the general population. Comorbid psychiatric comorbidity can complicate RA treatment decisions, leading to an increased likelihood of adverse outcomes, including reduced disease control, lack of quality remission, poor quality of life, and higher mortality. The purpose of the study is to create a screening - diagnostic model for predicting the mental state of patients with rheumatoid arthritis for the timely treatment of mental disorders. Methods. All patients underwent a clinical-psychopathological and clinical-catamnestic examination followed by dynamic observation and analysis of disease histories. At the same time, along with the general clinical examination, in order to identify psycho-emotional disorders, all patients underwent an experimental psychological study. The results. The proposed model for diagnosing and predicting the mental state of patients with rheumatoid arthritis consists of two algorithms: the algorithm for coding patients and the algorithm for determining and predicting the mental state of patients with rheumatoid arthritis. The new method makes it possible to speed up the determination of the mental state of a sick person without testing and take it into account in the treatment of the underlying disease.